Estimating Optimal Product Variety of Firms - Shiozawa, Yoshinori (Evolutionary and institutional economics review, 2012)
Product variety is a crucial dimension for successful management. While there are an enormous number of papers on this subject, few give insights on what to do on the estimation of optimal product variety in a concrete situation. Many results are much too sensitive to the assumptions and the conclusions are often contradictory. This paper presents a new method for estimating optimal variety for a firm. The estimation depends on the estimation of expected coverage function, which is defined in the paper. All the difficult problems in the optimal variety estimation are concentrated in the estimation of this function. But this allows people to discern what are crucial and what are not. The formula obtained here is simple and intuitive, and no similar formula has appeared before in the literature. It provides various hints to the optimal variety estimation by means of costs and sales expectations. The result can be extended to an oligopolistic competition case. The paper concludes by making a comparison with monopoly and oligopoly cases.